(untitled) (Orinoquia, 2016)
The chemical composition and antibacterial activity of essential oil from Minthostachys mollis were evaluated; the plants were grown in the Norte de Santander department, Colombia. The essential oil was obtained by conventional hydrodistillation from Minthostachys mollis leaves; relative density was determined at 20°C, as were the refraction index, essential oil solubility in ethanol (70% v/v) and optical rotation. Chemical composition was evaluated by gas chromatography/mass spectrometry (GC-MS). Three bacteria were used for evaluating antibacterial activity: Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 12228 and Escherichia coli ATCC 25922. The oil was diluted to the desired concentration (1,000-50 µg/mL) for determining antibacterial sensitivity and minimum inhibitory concentration, using the broth microdilution method, and a microplate reader was used for quantifying bacterial growth. Yield was 0.6%. Sensitivity test results revealed that bacteria were sensitive to essential oil from Minthostachys mollis; furthermore, this oil had a high content of oxygenated monoterpenes (i.e. carvacrol and thymol) having recognised antibacterial activity. It can thus be concluded that the vegetal species evaluated here is promising for controlling bacteria. Key words: Muña; essential oil; antibacterial activity.